Coronary artery anomalies: A multidisciplinary approach to shape the landscape of a challenging problem. (23rd June 2017) - Molossi, Silvana; Agrawal, Hitesh
Abstract: Coronary artery anomalies, particularly anomalous aortic origin of a coronary artery with an interarterial course, are associated with sudden cardiac arrest or death in the young. There is paucity of data on risk stratification and longitudinal follow up is lacking in these patients. Collaboration and sharing of data among specialized centers might shed much needed light in this complex problem.